2008
DOI: 10.1111/j.1365-3148.2007.00799.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Coa implicated in severe haemolytic disease of the foetus and newborn

Abstract: BACKGROUND Haemolytic disease of foetus and newborn (HDFN) is triggered by enhanced destruction of red blood cell due to immune-mediated destruction, intrinsic abnormalities, acquired aberrations, etc. Lifespan of infant's erythrocytes are shortened by the action of placentally transferred maternal antibodies in immune-mediated HDFN. The aim of this study was to identify the frequency of maternal antibodies in neonates with hyperbilirubinaemia. Settings and Design-This was a cross-sectional study in neonates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Unfortunately, a clear cutoff for anti-Co a antibody titres, leading to foetal anaemia, is lacking (de Haas et al, 2015). In our and other cases of severe foetal anaemia, the antibody titre was measured at a level of 1 : 128 in IAT and in a case of mild HDFN the titer was only 1 : 32 (Simpson, 1973;McIntyre et al, 1976;Michalewska et al, 2008). Here, however, it is important to consider the different methods of antibody titre determination used in the 1970s and nowadays.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Unfortunately, a clear cutoff for anti-Co a antibody titres, leading to foetal anaemia, is lacking (de Haas et al, 2015). In our and other cases of severe foetal anaemia, the antibody titre was measured at a level of 1 : 128 in IAT and in a case of mild HDFN the titer was only 1 : 32 (Simpson, 1973;McIntyre et al, 1976;Michalewska et al, 2008). Here, however, it is important to consider the different methods of antibody titre determination used in the 1970s and nowadays.…”
mentioning
confidence: 74%
“…This method was used in the four cases in the 1970s, but required repeated amniocentesis with the risks of an invasive procedure (Simpson, 1973;McIntyre et al, 1976;Fuhrmann et al, 1979). Measurement of the MCA-PSV is the gold standard nowadays and was performed in our and Michalewska's case (Mari et al, 1995;Michalewska et al, 2008). Compared with that case, where MoM-values for the MCA-PSV cutoff were used, we used the reference values published by Kurmanavicius et al (2001) (Mari et al, 1995).…”
mentioning
confidence: 99%
“…Using maternal blood for intrauterine or neonatal transfusion has been reported in some cases where blood lacking a high‐prevalence antigen could not otherwise be procured. These include a patient with anti‐Ku, 17 a patient with anti‐Jsb, 18 with anti‐Coa, 11 and a patient with anti‐Rh17 19 . In the latter case, maternal blood was ABO incompatible with the fetus, and a good outcome was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies have shown that anti-Co a and anti-Co b antibodies are able to reduce the survival of targeted erythrocytes [19][20][21][22][23]. There are also reports of auto-antibodies mimicking Colton specificities [24,25].…”
Section: Discussionmentioning
confidence: 99%